O2, dissolved inorganic carbon and CaCO3 fluxes and organic and inorganic production of rhodolith beds under future conditions - Kelly James; N A Kamenos; H L Burdett (PANGAEA, 2024)
The data includes measurements of oxygen (O2), dissolved inorganic carbon (DIC) and calcium carbonate (CaCO3) fluxes. Fluxes were obtained from in vitro incubations of rhodolith bed community samples. Samples were collected by hand using scuba from Loch Sween (Scotland; 56.031837, -5.601581; Water depth = 7m) and contained sediment (~8cm), with live coralline algae, macroalgae and calcifying fauna on the top of the sediment. Experiments were run in the summer and winter. Samples were collected on 2021/07/21 for the summer experiments and 2021/01/01 for the winter experiments. Separate mesocosms (referred to as cores) collected for each sampling campaign. Light and dark incubations were run for 2 hours. Net (daily) flux was calculated by multiplying light and dark incubations by the respective amount of hours spent in the light or dark. O2 fluxes were calculated by using optic spots, with O2 concentrations taken at the start and end of the incubation. DIC fluxes were determined by measuring the DIC concentration of water samples at the start and end of the incubation. DIC was determined using an Automated Infra-Red Inorganic Carbon Analyser (AIRICA). CaCO3 fluxes were calculated using the alkalinity anomaly technique with total alkalinity measured via titration. Information of flux calculations can be found in Martin et al. (2007; doi:10.3354/meps335019). All flux measurements were corrected for considering seawater blanks from both light and dark cores. O2 fluxes were used to calculate organic carbon (OC) production, and CaCO3 fluxes were used to calculate inorganic carbon (IC) production. Carbon Dioxide (CO2) drawdown was calculated as OC - IC, assuming that 1 mol of IC produced = 1 mol of CO2. Flux measurements were taken from 2021/09/07 - 2021/09/21 in the summer, and 2022/01/20-2022/01/31 in the winter. As experiments were run in the lab, conditions were maintained at treatment levels.The data was collected to determine if OC and IC production varied with global warming and ocean acidification and if that would change rhodolith bed communities capacity to act as a source or a sink.